The Existence of A Single Submission Online Institution in Land Technical Considerations - Susi Andriyani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The enactment of Government Regulation Number 24 of 2018 which introduced the Online Single Submission (OSS) institution brought many changes in various fields, one of which was in the field of land services. This study analyzes the implementation of land technical considerations through the OSS institution and the obstacles in the implementation of land technical considerations through the OSS institution. The research method used is normative legal research with a statutory approach and a conceptual approach. The results of the study indicate that the Implementation of Land Technical Considerations through the OSS institution is intended to provide convenience in obtaining permits in order to improve the investment climate in Indonesia.